Improving Clinician Adherence to Evidence-Based Recommendations Reduces Unnecessary ICD Shocks - Nierengarten, Mary Beth (MD Conference Express, 2013)
Late-breaking results from the prospective Shock-Less study indicated that providing clinicians with reports about implantable cardioverter defibrillator (ICD) programming improved adherence to shock-reduction guidelines in real-world practice settings, and significantly reduced the risk of unnecessary ICD shocks in patients.